Participatory digital approaches to embedding student wellbeing in higher education - Lister, Kate; Riva, Elena; Kukulska-Hulme, Agnes; Fox, Claudie (Frontiers in Education, 2022)
Student mental health and wellbeing are critical topics in higher education. In response to broader societal shifts in thinking around mental health and wellbeing, there are calls for universities to take a more proactive and holistic approach, working in partnership with students to embed mental wellbeing throughout learning, tuition and curricula. This paper presents two participatory projects from different UK higher education institutions, both of which took holistic, proactive and inclusive approaches towards supporting student mental wellbeing in higher education, using online and technology-based approaches. The first project is the digital ‘Wellbeing Pedagogies Library’ at the University of Warwick, a digital repository co-designed with students to foster the sharing of pedagogical practices that support student wellbeing, and to offer a practical support to students and staff who want to create and/or sustain wellbeing-inducing teaching and learning environments. The second project is the ‘Mental Wellbeing in Distance Learning’ project at the Open University, which piloted five digital subprojects, led by different practitioners in partnership with students, aiming to address barriers to wellbeing in different aspects of distance learning. This paper presents the participatory methods and approaches from each project, explores stakeholders’ perceptions of the value that participatory approaches added to the projects, and comparatively evaluates the projects’ outcomes in order to draw conclusions that can inform future participatory research. In doing so, it explores different types of participatory approaches that can be taken in different contexts, and how terms such as 'holistic', 'proactive' and 'inclusive' may be interpreted and applied in practice. Drawing on the findings, it posits that participatory approaches and partnerships with students should be considered a priority when designing digital resources, interventions and solutions to support student mental wellbeing.